2023
DOI: 10.1039/d3nr02342g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast glimpses of the excitation energy-dependent exciton dynamics and charge carrier mobility in Cs2SnI6 nanocrystals

Abstract: Advancements in photovoltaic research suggest tin-based perovskites as potential alternatives to traditional lead-based structures. Cs2SnI6, specifically, stands out as a notable candidate, exhibiting impressive performance. Nevertheless, its complete potential remains...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…{CsI þ SnI 2 þ I 2 -, [16] CsI þ SnI 2 -, [35,36,46,[67][68][69] CsI þ SnI 4 - [32,38,46,[70][71][72] }; Solution based methodnanocrystal! { [18,73,[76][77][78][79][80]87,89] }; Vacuum based method {AACVD-, [14] Co-evaporation-, [81][82][83] 2-Step method- [29,33,34,45,[84][85][86] }. The asterisk sign represents usage of additional HI precursor during synthesis.…”
Section: Solution-based Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…{CsI þ SnI 2 þ I 2 -, [16] CsI þ SnI 2 -, [35,36,46,[67][68][69] CsI þ SnI 4 - [32,38,46,[70][71][72] }; Solution based methodnanocrystal! { [18,73,[76][77][78][79][80]87,89] }; Vacuum based method {AACVD-, [14] Co-evaporation-, [81][82][83] 2-Step method- [29,33,34,45,[84][85][86] }. The asterisk sign represents usage of additional HI precursor during synthesis.…”
Section: Solution-based Methodsmentioning
confidence: 99%
“…The exciton dynamics in Cs 2 SnI 6 nanocrystals were recently studied by G. Kaur et al using the steady-state absorption spectroscopy technique with a reported experimental band-gap value of 1.71 eV, and the presence of two distinct exciton peaks A and C at energies E A = 1.93 eV and E C = 3.44 eV, respectively, along with a less prominent B peak corresponding to E B = 2.74 eV (see Figure 2a) is identified. [87] The physical origins of the same are ascribed to specific transitions (V j C k ) from jth valence band (V) to kth conduction band) in its theoretically calculated electronic band structure, where j = 1 corresponds to the highest occupied band and k = 1 points to the lowest unoccupied band (see Figure 2b). The theoretical band-gap calculations reveal a band-gap of 1.03 eV, and the appearance of A, B, and C excitonic peaks is due to V 2 C 1 transition at Γ-point for peak-A (E A = 1.45 eV); V 4 C 1 transition at L-point for peak B (E B = 2.30 eV); and V 10 C 1 transition at X-point for C-peak (E A = 3.7 eV), respectively.…”
Section: Complex Absorption Spectra Of Cs 2 Snimentioning
confidence: 99%
See 2 more Smart Citations